Культура как основа качества социального образования - Жиров, М. С. (НТУ "ХПИ", 2010)
У статті розглянуто проблему культурологічної компетентності соціального працівника і її структуру. Проаналізовано взаємозв'язок соціалізації і культури в рамках становлення особистості як суб'єкта суспільного розвитку. Досліджено поняття “культура” у працях видатних педагогів і філософів, а також проаналізовано основні напрями розвитку освіти як соціокультурного чинника. Висвітлено практичну діяльність науково-навчального центру соціокультурних досліджень, який покликаний реалізувати нову культурно-освітню ідею, співвіднесену з реальними можливостями й умовами її здійснення в конкретному соціокультурному середовищі.

In the article the problem of culturological competence of social worker and its structure is considered. Intercommunication of socialization and culture within the framework of becoming of personality as a subject of public development is analyzed. Notion of “culture” in labors of prominent teachers and philosophers is explored, and also basic directions of development of education as a socio and culturological factor are analyzed. Practical activity of scientifictraining center of socio and culturological researches, which is called to realize a new culture and educational idea correlated with the real possibilities and terms of its realization in a concrete socio and culturological environment is lighted up.
Сulture as a basis of the quality of social education
Keywords: самоидентификация; компетентность; культурологическая ориентированность; формы культуры; ценности; социальная служба